A study of young people’s attitudes towards the impact of the fashion industry on the environment - A. N. Timokhovich; Ts. S. Filenko; A. S. Lelyakova (Вестник университета)
This article presents the results of an empirical study aimed at studying young people’s attitudes to the impact of the fashion industry on the environment. The survey is used as a research method. The study was conducted in the spring of 2023. As a result of the study, a high degree of awareness of young people about the negative impact of the fashion industry on the environment was revealed; the attitude of young people to the manifestations of the fashion industry was revealed; the willingness of young people to change their consumer practices in the fashion industry was determined; aspects of the behavior of young people associated with following eco-friendly principles (higher awareness when consuming industry goods fashion; more rare purchases of fashion industry products; rejection of genuine leather and fur in clothing; reduction of consumption of various goods; the purchase of goods in eco-friendly/recyclable packaging; focus on the purchase of eco-friendly products; the delivery of personal belongings for recycling; the use of second-hand goods); the positive attitude of young people to the types of activities that can be carried out by companies in the fashion industry aimed at solving environmental problems has been revealed.